Chester and Mary Root with a typewriter - Unknown:::Creator::::::::::::
Photograph shows Chester and Mary Root each with a finger on a key of an old typewriter that is sitting on the reception desk in the YWCA building on Second Street. There is a woman watching them from the other side of the counter and another woman sitting in the background. They are attending the 1973 YWCA annual meeting.